Simulation of flexural behavior of a simply supported beam subjected to corrosion - Mahadik, Vinay; Sharma, Akanshu; Ožbolt, J.; Parulekar, Y.M.; Reddy, G.R. Reddy; Vaze, K.K. (Journal of Structural Engineering, 2024)
Development of a reliable procedure for numerical modeling of the effect of corrosion on the structural behavior of reinforced concrete is a prime concern of the various researchers working in this area. In the present study, an attempt is made to numerically simulate one of the experiments performed at LMDC on identical corroded and non-corroded beams. A generalized modeling of the corrosion effect, with uniform corrosion assumption seems inadequate. It is found that consideration of localized modeling of pitting of the reinforcement is essential for better numerical solution. Further, the significance of deterioration of concrete due to exposure to corrosive environment on the behavior of the beam is also highlighted.